Indentation recovery threshold using the Electrostatic Detection Apparatus®. Issue 1 (2nd January 2017) - Roloff, Bente; Offa, Bethan; Turner, Ian J.
ABSTRACT: The Electrostatic Detection Apparatus® (ESDA) is an instrument employing techniques used by Questioned Document Examiners (QDE) for the development of indented impressions. It has been reported that impressions can be recovered from between three and five sheets beneath the original writing; however, there have been limited studies on the impact of paper type in this process. In this experiment, paper densities ranging from 54–170 g/m 2 were examined and evaluated using a standard ESDA® protocol. Paper density affects both the quality and the depth at which an underlying impression can be visualized by electrostatic methods (between one and five sheets). Knowing the paper density could aid QDE in the effective examination of documents for impressions.